Lexicography : an introduction - Jackson, Howard, 1945- (Routledge, 2002)
This book is an accessible introduction to lexicography - the study of dictionaries. Dictionaries are used at home and at school, cited in law courts, sermons and parliament, and referred to by crossword addicts and Scrabble players alike. Lexicography provides a detailed overview of the history, types and content of these essential references. Howard Jackson analyzes a wide range of dictionaries, from those for native speakers to thematic dictionaries and those on CD-ROM, to reveal the ways in which dictionaries fulfil their dual function of describing the vocabulary of E.